2019
DOI: 10.1186/s11671-019-3051-6
|View full text |Cite
|
Sign up to set email alerts
|

Modifying Reduced Graphene Oxide by Conducting Polymer Through a Hydrothermal Polymerization Method and its Application as Energy Storage Electrodes

Abstract: We report chemical in situ deposition of conducting polymer poly (3,4-ethylenedioxythiophene) (PEDOT) on reduced graphene oxide (rGO) nanosheets through a simple hydrothermal polymerization method. The functional groups on graphene oxide (GO) were directly employed as an oxidant to trigger the polymerization of 3,4ethylenedioxythiophene (EDOT), and the GO nanosheets were reduced into rGO accordingly in an aqueous environment. Well anchoring of ultrathin PEDOT on rGO through this oxidant-free method was confirm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 76 publications
(17 citation statements)
references
References 74 publications
1
12
0
Order By: Relevance
“…Figure 2 (f and g) show the high-resolution XPS spectra of the S 2p and Ti 2p regions, respectively. The S 2p spectrum reveals the presence of four separate peaks, which are related to S 2p 3/2 (162.2 eV), S 2p 1/2 (163.9 eV), S 2p 2/3 (166.5 eV), and S 2p 1/2 (167.9 eV) 44,45 . The Ti 2p spectrum (Fig.…”
Section: Analytical Characterizationmentioning
confidence: 99%
“…Figure 2 (f and g) show the high-resolution XPS spectra of the S 2p and Ti 2p regions, respectively. The S 2p spectrum reveals the presence of four separate peaks, which are related to S 2p 3/2 (162.2 eV), S 2p 1/2 (163.9 eV), S 2p 2/3 (166.5 eV), and S 2p 1/2 (167.9 eV) 44,45 . The Ti 2p spectrum (Fig.…”
Section: Analytical Characterizationmentioning
confidence: 99%
“…Besides, the CV measurement of the GPNVP composite was performed at a scan rate of 50 mV/s up to 1000 cycles and the corresponding results are shown in Figure S5. The shape and area of the CV curves are comparable even after 1000 cycles (Figure S5), which demonstrates the good rate capability and good electrochemical resistance of the GPNVP composite after many cycles [67]. Moreover, these results suggest that the resulting GPNVP composite electrode could be ideal for various electrochemical applications.…”
Section: Resultsmentioning
confidence: 67%
“…On the other hand, other authors have reported an enhanced capacitance of reduced graphene oxide in comparison to graphene oxide [60,61]. The latter can be related to: (i) an increase of the electrical conductivity upon hydrothermal reduction, which favours the electron mobility at RGONF electrodes [61][62][63], and/or (ii) the particular porous texture and turbostratic structure of RGONFs, which is less restrictive for ion/electrolyte transport. In this context, an important recovery of the π-π* shake-up satellite contribution was observed by XPS (Table 2) upon hydrothermal reduction, as well as a progressive removal of oxygenated species, which may lead to an improved carbon conductivity [7].…”
Section: Electrochemical Characterization Of Gonf and Rgonfsmentioning
confidence: 97%